Assessment of Knowledge, Attitude, and Practice (KAP) as well as facilitators and barriers in reporting adverse drug reactions among health care professionals at a neonatal intensive care unit in Qatar (Journal of Pharmaceutical Negative Results, 2023)
Aim: This study examined healthcare providers' knowledge, attitude, practice, as well as facilitators and barriers to adverse drug reaction reporting in Qatar's largest tertiary care neonatal intensive care unit, WWRC.Method: A cross sectional survey for health care professionals (Physicians, nurses and Pharmacists) was conducted for a period of one year (January to December 2021).The sample size was computed using an online (Raosoft® calculator).The data was coded entered and analysed using SPSS (version 20).The data was analysed using descriptive and inferential statistics.Result: The response rate was 53.6% (222/414). The majority of the respondents were females(87.4%) with at least a bachelor’s degree (53.6%) and predominantly nurses(81%). While a majority of the participants felt it was their professional duty to report ADRs (96.4%), most of them responded “no” to having reported any ADR in the past (77%) and also said ‘no’ to having witnessed any ADR in the past 12 months (89.6%). In our study, ADR monitoring and reporting practices were strongly correlated with different strata of HCPs. Compared to physicians and nurses, clinical pharmacists were more likely to report adverse drug reactions (mean SD60.1 ± 7.1) (p= <0.05) in the NICU. No other characteristics, including knowledge, attitude, or facilitators and barriers, were found to have a statistically significant relationship with demographic variables of healthcare providers reporting ADRs in the NICU. The scale investigating determinants linked to ADR reporting has high internal consistency, with Cronbach’s Alpha coefficient reported 0.81. Our analysis revealed that knowledge and training, patient safety, professional duty, and social influence had more positive views, while poor feedback post-reporting had more negative views. Key facilitators to reporting were to improve patient safety and feeling of professional liability; however, the main barriers reported were lack of time, poor feedback, and a complex reporting process.Conclusions: According to the current study, clinical pharmacists promote ADR reporting and have better practice characteristics than other HCPs. All HCPs has positive knowledge and attitude toward ADRS reporting. The study found several NICU ADR reporting facilitators and barriers. Poor feedback, time constraints, complex reporting forms, and reporting procedures are primary ADR reporting issues. These findings will help build theoretically informed strategies to improve ADR reporting and patient safety. Given these findings, NICU HCPs need pharmacovigilance education, training, and empowerment.